Silent Songs of Kolbano : Messages And Meanings In Dawan Death Speech Tradition In South Pene Kolbano Subdistrict South Central Timor Regency: English - Sabuna, Fodita; Anabokay , Yanrini Martha; Isu, Rudolof Jibrael (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
This study explores the "Function, Meaning, and Value of the Death Speech of the Dawan Ethnic Group in South Pene Village, Kolbano Subdistrict, South Central Timor Regency." The death speech is a central element of funeral rituals, serving as a medium for cultural, social, and spiritual expression. The research employs a descriptive qualitative method, with data gathered through observation, interviews, and documentation. The analysis is grounded in cultural linguistics, Jakobson’s theory of language functions, and Alisjahbana’s classification of values. Findings reveal that death speech performs multiple essential functions: guiding the soul to the ancestral realm (spiritual), uniting the community in mourning (social), affirming inheritance rights (customary), conveying moral lessons (educational), and preserving cultural identity (cultural). It embodies symbolic, religious, historical, and genealogical meanings and reflects the core values of Dawan life. The study concludes that death speech is not merely a traditional practice but a vital form of intangible cultural heritage that must be preserved and passed on to future generations.